Balloon catheters for induction of labor at term after previous cesarean section: a systematic review - Kehl, Sven; Weiß, Christel; Rath, Werner (European journal of obstetrics & gynecology and reproductive biology, 2016)
To systematically review the application of balloon catheters for cervical ripening and labor induction at term after previous cesarean section. All pregnancies at term with previous cesarean section were included when cervical ripening or labor induction was conducted with balloon catheters. MEDLINE, Cochrane database and bibliography of identified articles were searched for English language studies. Reviews and meta-analysis, randomized and non-randomized controlled trials, prospective and retrospective cohort studies as well as case-control studies were considered. A total of 48 potentially relevant studies were identified. The title and abstract were screened for eligibility and 32 articles were excluded. The remaining 16 publications included 1447 women (single-balloon catheter: n=1329, double-balloon catheter: n=118). There were no randomized controlled trials. Most of the trials were retrospective studies (n=10). The rate of uterine rupture after labor induction was low (n=18, 1.2%). Meta-analysis of studies comparing the risk of uterine rupture between labor induction and spontaneous onset of labor found a higher risk after induction (OR 2.45, 95%CI 1.34-4.47, NNH 186). The average rate of oxytocin application was 68.4%, and vaginal birth was achieved in 56.4%. The risk for cesarean delivery was higher when labor was induced (OR 2.63, 95%CI 2.24-3.10). Data on balloon catheters for labor induction after previous cesarean section are limited by small sample size and retrospective analyses. The present data show a moderately increased risk for uterine rupture (OR=2.45) compared to spontaneous onset of labor. However, for evidence based recommendations much more well-conducted trials are needed.
Gesehen am 06.08.2019
Available online 3 August 2016